2021
DOI: 10.1186/s10086-021-01968-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slenderness ratio and sectional geometry on the axial compression behavior of original bamboo columns

Abstract: Bamboo has been widely used as a load-bearing material in construction; however, there are limited studies on the stability of slender original bamboo columns. Based on the experimental investigation of thirty-nine original bamboo columns, parametric analyses were conducted to investigate the influence of the diameter–thickness ratio, cross-sectional area and slenderness ratio on the axial compression behavior of original bamboo columns. The test results indicate that the failure modes of the columns are subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…It was observed that bamboo has excellent ability to resist buckling when subjected to bending and shear [23] and local buckling is not considered as a critical mechanism [50]. As local buckling depends on adjusting the slenderness ratio and diameterthickness ratio [51], the tapering structure of bamboo would be the cause of this ability. Therefore, future study should consider the relationship between the tapering structure of bamboo and the critical moment for local buckling.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that bamboo has excellent ability to resist buckling when subjected to bending and shear [23] and local buckling is not considered as a critical mechanism [50]. As local buckling depends on adjusting the slenderness ratio and diameterthickness ratio [51], the tapering structure of bamboo would be the cause of this ability. Therefore, future study should consider the relationship between the tapering structure of bamboo and the critical moment for local buckling.…”
Section: Discussionmentioning
confidence: 99%
“…Contoh uji berukuran penuh yang diberikan satu beban terpusat dikategorikan sebagai balok pendek (RB≤10). Rasio kelangsingan yang berkisar antara 10 hingga 20, spesimen menunjukkan karakteristik balok atau kolom pendek [48]. Nilai RB contoh uji berukuran penuh pada pengujian ini dipengaruhi oleh ukuran penampang balok dan tumpuan lateral.…”
Section: Faktor Stabilitas Balok (Cl)unclassified
“…Bamboo is considered a new material with great market potential among natural fibers [ 24 , 25 , 26 , 27 ] and has been widely used in civil engineering structures, such as short-span footbridges, low-rise houses, long-span roofs and construction envelopes [ 28 , 29 , 30 , 31 ]. The original bamboo tube, as a natural fiber tube structure, has attracted the attention of scholars [ 32 , 33 , 34 ]. Umer et al [ 35 ] investigated the energy-absorbing characteristics of a range of lightweight bamboo-reinforced foam structures.…”
Section: Introductionmentioning
confidence: 99%